2001
DOI: 10.1091/mbc.12.5.1519
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-independent Survival of Human Keratinocytes through an EGF Receptor/MAPK-Kinase-dependent Pathway

Abstract: Normal epithelial cells undergo apoptosis when they are denied contact with the extracellular matrix, in a process termed "anoikis." Conversely, malignant epithelial cells typically acquire anchorage independence, i.e., the capacity to survive and grow in the absence of matrix interaction. Here we asked the question whether anoikis is affected by signaling through the EGF receptor (EGFR). We focused on the EGFR because EGFR signaling is frequently deregulated in malignant epithelial cells. We demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
98
0
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(107 citation statements)
references
References 42 publications
8
98
0
1
Order By: Relevance
“…We described previously that EGFR-dependent Bcl-x L expression is required for matrix-independent HaCaT cell survival (Jost et al, 2001b;Rodeck et al, 1997). Furthermore, Bcl-x L expression in these cells is controlled, in part, by MEK/ MAPK signaling (Jost et al, 2001a). Consistent with a role of MTA1 in EGFR-dependent Bcl-x L regulation we observed that inhibition of EGFR activation was associated with reduced MTA1 expression in HaCaT keratinocytes.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…We described previously that EGFR-dependent Bcl-x L expression is required for matrix-independent HaCaT cell survival (Jost et al, 2001b;Rodeck et al, 1997). Furthermore, Bcl-x L expression in these cells is controlled, in part, by MEK/ MAPK signaling (Jost et al, 2001a). Consistent with a role of MTA1 in EGFR-dependent Bcl-x L regulation we observed that inhibition of EGFR activation was associated with reduced MTA1 expression in HaCaT keratinocytes.…”
Section: Discussionsupporting
confidence: 85%
“…Importantly, survival of HaCaT-MTA1-S cells was similarly diminished by EGFR blockade suggesting that MTA1 expression alone is not su cient to relieve the requirement for EGFRderived signals for cell survival in the anchorageindependent state. Consistent with earlier results (Jost et al, 2001a) addition of EGF to the culture medium during suspension culture markedly improved survival of HaCaT-MTA-S cells (Figure 5b). However, overexpression of MTA1 antisense sequences obviated EGFdependent HaCaT cell survival in forced suspension culture indicating that MTA1 expression is essential to EGFR-dependent HaCaT cell survival in suspension culture.…”
Section: Mta1 Protects Keratinocytes From Anoikissupporting
confidence: 92%
See 2 more Smart Citations
“…This was accomplished by maintaining keratinocytes for up to 72 h in suspension on top of a 0.9% agarose gel. We have shown previously that this treatment induces extensive apoptosis of primary human keratinocytes within 24 to 48 h. 25 This was confirmed by assessing PARP cleavage, which occurred within 48 h of forced suspension culture ( Figure 4B). However, no cleavage of procaspase-14 was observed throughout the observation period.…”
Section: Lack Of Procaspase-14 Processing During Keratinocyte Apoptosissupporting
confidence: 74%